Tinjauan Ekonomi Islam Tentang Perilaku Konsumen Apotek Barokah Kaliboto Pasca Pemberhentian Aturan Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) - Mohammad Saiful Rifai (Universitas Muhammadiyah Ponorogo, 2023)
The COVID-19 pandemic has caused many changes in various sectors, one of which is the economic sector related to consumer behavior. The purpose of this study is to find out Islamic Economic Review of Pharmacy Consumer Behavior After the Dismissal of Rules for the Implementation of Restrictions on Community Activities. The approach used is a phenomenological approach with a type of field research using descriptive qualitative methods. The results showed that during the COVID-19 pandemic that During the Covid-19 pandemic, consumers became concerned about health by buying various products such as vitamins, masks, and hand sanitizers. This lifestyle also carried over until the pandemic ended but with normal volume. According to the Islamic economic review, consumption activities must indeed be carried out as needed and not excessive. In addition, it must also pay attention to aspects of halal and benefit and this is in accordance with what is done by consumers of the Barokah Kaliboto Blitar pharmacy.